Application of Static Stretching Movement Variations Based on Student Engagement in Sports Education Learning - Albani, Iqbal Akbar; Kurniawan, Ari Wibowo; Setyo Pramono, Abdul Hadi; Clarita, Tya (UNIVERSITAS NEGERI MAKASSAR, 2024)
Stretching is the basis of the exercise process, exercising without stretching can trigger several health problems in the body. In sports learning, statistical stretching can increase the feeling of dread before exercise, but it seems monotonous and boring compared to dynamic stretching. This study aims to apply a variety of statistical stretching movements and test their effectiveness. The method used in this research is experimental research using a one-group pretest-posttest design. Data collection techniques were carried out using several research instruments including observation sheets, pretest posttest questionnaires, and fitness test assessments. Meanwhile, data analysis techniques were carried out using the T-test and the Komologrow-Smirnov test. The results of the study showed an increase after treatment of almost 2.275% compared to before treatment. Apart from that, if tested using the T-test, it is known that the significance results show a value of 0.0008 which is smaller than the normality rule of 0.05 so Ho can be rejected and Ha is accepted so it can be concluded that this research on the application of variations in statistical stretching movements is very effective in Sport Education Learning or known as PJOK.